Spatial pattern and its development in mid- to late-successional tree communities in unmanaged boreal forests in northern Finland - Kreutz, Andreas (Helsingfors universitet, 2013)
This study examined the development of tree communities from mid- to late-successional stages in unmanaged Hylocomium-Myrtillus (HMT) forests in northern Finland using a chronosequence approach. More specifically, this thesis adressed the following study questions: (1) What is the spatial pattern of the overall tree community and does this overall pattern changes as the forest`s successional stage changes from mid- to late-successional? (2) What are the spatial patterns of small and large trees and how they differ from mid- to late-successional stages? (3) Is the occurrence of P. abies is related to Betula spp. in mid- to late-successional stages and does this potential relation changes as the forest`s successional stage changes from mid- to late-successional? (4) Does the tree population displays a mosaic of small patches of P. abies and Betula spp. trees over succession from mid- to late-successional stages? The study was carried out in the Värriö Strict Nature Reserve in north-eastern Finland in 2011. Living and dead trees were recorded within 3 transects (300 m long, 40 m wide) in 3 different stands representing differing midto late-succesional stages from 180 years to at least 350 years. The stands were classified according to their species composition in Betula spp. dominated, mixed P. abies-Betula spp. and P. abies dominated. Finally, spatial patterns were analysed using Ripley`s K-function. The spatial tree patterns were predominantly clustered and this pattern did not vary much over succession. Small trees were generally more clustered than larger trees and regular distributions did not occur. Saplings of both species were predominantly attracted to mature trees of the same species. This, and the repulsion between living mature P. abies and mature Betula spp. suggests clumps composed of only one species and thereby a mosaic of small patches of P. abies and Betula spp. in mid- to late-successional forest stages. At the same time, a successive dependency of P. abies on Betula spp can be rejected. The lack ...